Electrochemical ultra-micro sensors for the determination of synthetic and natural antioxidants in edible vegetable oils - Robledo, Sebastian Noel (2014)
We describe the application of square wave voltammetry at ultramicroelectrodes for the determination of natural antioxidants (α, δ, and γ tocopherols), and tert-butyl hydroxytoluene in edible vegetable oils. Tocopherol determinations were performed in benzene/ethanol (1:2) + 0.1 mol L-1 H2SO4 + oil samples at a carbon fiber disk ultramicroelectrode, and tert-butyl hydroxytoluene was determined in acetonitrile (ACN) + 0.1 mol L-1 (C4H9)4NF6P at a Pt band ultramicroelectrode after performing its extraction from the oil sample with ACN. Recovery percentages determined by the standard additions method were in the range from 92% to 102 %, with variation coefficients between 0.5% and 4%. Antioxidant concentrations calculated by this methodology were in good agreement with those values declared by the manufacturers.